Fetal Programming of Brain and Behavior through Ionizing Radiation - Christine Lalonde; Douglas Boreham; T. C. Tai (Stresses, 2023)
For decades, the Barker hypothesis and thrifty phenotype hypothesis have driven researchers to explore the development of metabolic syndrome through fetal programming. In this short review, we provide peer-reviewed support for the fetal programming of neural genetic activity and behavior in multiple neural regions: the prefrontal cortex, the cerebral cortex, the hippocampus, the cerebellum, and the hypothalamic–pituitary–adrenal axis. We also introduce ionizing radiation as a purported indirect driver of phenotypical changes. The predisposition of brain and behavioral phenotypes after gestational exposure to stressors can lead to aversive and harmful outcomes, rather than protective adaptations.